A short communication on indoor-based therapies to reduce stress during the COVID-19 pandemic - Karam Singh, Daljit Singh; Rajoo, Keeren Sundara; Muharam, Farrah Melissa; Zulperi, Dzarifah (JACS Directory, 2020)
Preserving mental health during the COVID-19 crisis should be a priority for individuals worldwide. In this regard, mental health professionals should advise the general public on the actions/activities that they can take to prevent mental health issues from becoming the next pandemic. However, the general public should also actively take measures to improve their mental wellbeing. Music therapy, aromatherapy or indoor nature therapy may or may not have the potential to preserve mental wellbeing, but individuals should experiment with them to ascertain the effects on themselves. Moreover, the guidelines provided by WHO should also be adhered to, as a healthy mind starts with a healthy body.